3(2x-1)-3(4-2x)=6

Simple and best practice solution for 3(2x-1)-3(4-2x)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2x-1)-3(4-2x)=6 equation:


Simplifying
3(2x + -1) + -3(4 + -2x) = 6

Reorder the terms:
3(-1 + 2x) + -3(4 + -2x) = 6
(-1 * 3 + 2x * 3) + -3(4 + -2x) = 6
(-3 + 6x) + -3(4 + -2x) = 6
-3 + 6x + (4 * -3 + -2x * -3) = 6
-3 + 6x + (-12 + 6x) = 6

Reorder the terms:
-3 + -12 + 6x + 6x = 6

Combine like terms: -3 + -12 = -15
-15 + 6x + 6x = 6

Combine like terms: 6x + 6x = 12x
-15 + 12x = 6

Solving
-15 + 12x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + 12x = 6 + 15

Combine like terms: -15 + 15 = 0
0 + 12x = 6 + 15
12x = 6 + 15

Combine like terms: 6 + 15 = 21
12x = 21

Divide each side by '12'.
x = 1.75

Simplifying
x = 1.75

See similar equations:

| 3y/4-4=8 | | (2x-29)+(x+5)=180 | | 8v+2-3v-6= | | 0.8+0.2-5x= | | 16x+112=64+132x+14x | | 8+4(z-2)=-5x+8 | | x+0.2-5x= | | -6(x+2)+15=-4x-7 | | 3.2=4.4-0.3x | | (7x+1)+(13x+9)=90 | | 2(4-3x)-10=2x-74 | | 4x^3-9x^2-2=0 | | 13y-1.8=-5y+3.6 | | 4(5c+1)-26=17c+2 | | 33t=-46 | | X*.6=25 | | 5√6/4√50 | | 3x-8=4(x+4) | | 3m-7+m+23= | | 3x+29=6x+8 | | 4(x-3)=x-12 | | 8x%3-2x%4=-14 | | 4x-27andX+39= | | -11n-7=11 | | k/6-7=-4 | | 2(2x+5)+2x=250 | | 6x-15=5x+6-2x | | 1/2in(e^6) | | (5√6)/(4√50) | | (12n+99)+(8n+8)= | | 20n-16=0 | | 35x^3+63x^5+21x^6= |

Equations solver categories